Potential radiological impact of the phosphate industry in South Africa on the public and the environment (Paper 1). (June 2020) - Louw, I.
Abstract: Phosphate rock is mined on a large scale as a source material for fertilizers and other phosphorous containing products, such as phosphoric acid and gypsum. The potential problem of high concentrations of naturally occurring radionuclides in the phosphate industry has been recognized for many years. The industry is responsible for the production of millions of tons of phosphogypsum waste, which is usually stockpiled and might impact the surrounding environment. The presented study aims to assess the natural radioactivity concentrations in raw and waste sub-products from phosphate mining and fertilizer production in South Africa and determine the potential radiological risk associated with the industry. Activity concentrations of 238 U, 226 Ra and 232 Th in phosphate rock, phosphogypsum, tailings, fertilizer, soil and sediment were found to be similar to values reported in previous studies conducted in South Africa. Concentrations of the 232 Th decay series were higher than those of the 238 U series in rock and ore. The low concentrations of 238 U and 226 Ra in rock and ore, compared to other countries, makes it more suitable to be used for fertilizer production, and therefore increases the demand for export of rock phosphate and fertilizer from South Africa. 228 Ra concentrations in phosphogypsum were higher than 226 Ra. The activity of 228 Ra was also enriched compared to 232 Th, with a ratio of 0.45–19.8. Similar equilibria as described in literature were observed, with almost all the 228 Ra and 226 Ra present in the phosphate rock observed in the phosphogypsum. Only a low percentage of 232 Th present in the original rock remained in the phosphogypsum, with more than 60% present in the fertilizer. The activity concentrations of all nuclides in the analysed samples from the phosphate industry were less than the 1000 Bq kg −1 exclusion value proposed internationally for regulation of NORM. With the exception of phosphate rock samples, concentrations in all solids were lower than the 500 Bq kg −1 limit proposed by the National Nuclear Regulator in South Africa. The obtained values of Raeq for all phosphogypsum, tailings and soil samples were less than the recommended limit of 370 Bq kg −1 . The gamma index for the majority of samples was less than 0.5. The index exceeded the limit of unity only for phosphate rock and fertilizer samples, indicating some radiological risk to people living in the vicinity of the industry. The results suggested that members of the public were unlikely to receive any significant dose from the use of phosphate rocks and fertilizers, with an annual effective dose of less than 0.5 mSv.a −1 . The highest external dose of 0.45 mSv a −1 is expected from phosphate rock. The suitability of use of phosphogypsum as building material was evaluated. Based on the calculated gamma index [ I γ = 0.52 ± 0.14] use of phosphogypsum as building material is permitted. Highlights: Characterization of natural radioactivity in samples from the phosphate fertilizer production industry in South Africa. Comparison of measured activity concentrations in these samples with those in similar products worldwide. Evaluation of the radiological impact associated with the phosphate industry in South Africa. Evaluation of utilization of by-products such as phosphogypsum as building material.